The Role of Value For Money in Public Sector Financial Performance - Yap, Nonni (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
This study aims to determine the role of value for money in the performance of the public financial sector. Value for money is a management concept of public sector organizations which is based on three main elements, namely economy, efficiency, and effectiveness. The type of research used in this study uses qualitative methods. Data obtained through interviews, observation, and document studies, as well as case studies. The results of the study reveal that the results of the observations made explain inequality and the threat of the concept of the value of money that affects the performance of the public financial sector. To ensure the implementation of public responsibility by government agencies, it is necessary to improve the system, not only conventional audits but also value for money in conventional audits.